Artemisia Sieberi bess. subsp. sieberi a new record for Turkey and a delete record for Turkey Artemisia herba-alba asso. (Asteraceae) - Kurşat, Murat; Civelek, Şemsettin; Turko?lu, Ismail; Tabur, Selma (My University, 2011)
In the revision study on the genus Artemisia L. in Turkey, we observed that there were differences between the descriptions of Artemisia herba - alba Asso. in Flora Europea and Flora of Turkey and that the description of Artemisia herba - alba Asso. in Flora of Turkey was problematic. We observed that the Turkish specimens were the same as the specimens called Artemisia sieberi Bess., which were collected from Siberia, Caucasia, Central Asia and Kazakhstan. We found that our specimens matched the descriptions given for Artemisia sieberi Bess. in Flora of Iranica and Flora of Ussr. Thus, we determined that the species of Artemisia herba - alba Asso. wasn't found in Turkey and the specimens given as Artemisia herba -alba Asso. in Flora of Turkey were Artemisia sieberi Bess. subsp. sieberi which is a new record for the Flora of Turkey. The description, distribution map in Turkey and photography of Artemisia sieberi Bess. subsp. sieberi are given.
Keywords: Artemisia; Artemisia herba-alba; Artemisia sieberi; Asteraceae